2019
DOI: 10.1186/s12909-018-1417-6
|View full text |Cite
|
Sign up to set email alerts
|

The development and implementation of a 12-month simulation-based learning curriculum for pediatric emergency medicine fellows utilizing debriefing with good judgment and rapid cycle deliberate practice

Abstract: BackgroundThere are currently training gaps, primarily procedural and teamwork skills, for pediatric emergency medicine (PEM) fellows. Simulation-based learning (SBL) has been suggested as an educational modality to help fill those gaps. However, there is little evidence suggesting how to do so. The objective of this project is to develop and implement an SBL curriculum for PEM fellows with established curriculum development processes and instructional design strategies to improve PEM fellowship training.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
11
0
3
Order By: Relevance
“…Second, we heavily leveraged technology through an online learning management system to administer key elements of our course. In recent years there has been increasing recognition of the need to apply technology to develop collaborative networks to improve patient care in the emergency setting and beyond 36‐41 . In 2018 Barata et al 39 published the results of their consensus conference “Aligning the Pediatric Emergency Medicine Research Agenda to Reduce Health Outcome Gaps.” The authors recommended that technology and collaborative networks be utilized to generate and disseminate pediatric knowledge and prepare EDs to care for acutely ill and injured children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we heavily leveraged technology through an online learning management system to administer key elements of our course. In recent years there has been increasing recognition of the need to apply technology to develop collaborative networks to improve patient care in the emergency setting and beyond 36‐41 . In 2018 Barata et al 39 published the results of their consensus conference “Aligning the Pediatric Emergency Medicine Research Agenda to Reduce Health Outcome Gaps.” The authors recommended that technology and collaborative networks be utilized to generate and disseminate pediatric knowledge and prepare EDs to care for acutely ill and injured children.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there has been increasing recognition of the need to apply technology to develop collaborative networks to improve patient care in the emergency setting and beyond [36][37][38][39][40][41]. In 2018 Barata et al39 published the results of their consensus confer-…”
mentioning
confidence: 99%
“…The confidence question asks learners what their confidence is to perform a primary and secondary survey before and after the simulation session published about the application of RCDP to pediatric trauma care education [11,13]. The one other published work involving RCDP in pediatric trauma education described a longitudinal simulation curriculum for pediatric emergency medicine fellows, with one trauma case in a 12 month curriculum [16]. Additionally, RCDP is useful when there are significant time limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation has been shown to improve test scores in surgical residents 3 and to reduce training gaps in pediatric emergency medicine (PEM) fellows. 4 Additionally, many studies report that simulation-based curricula have helped improve self-confidence in surgical residents, 5 obstetrics residents, 6 and pediatric critical care fellows. 7 In choosing relevant topics, our findings showed that most interns did not feel confident performing even the initial steps of stabilization of asthma exacerbations (50%) or severe sepsis (69%).…”
Section: Introductionmentioning
confidence: 99%